1992
DOI: 10.1123/apaq.9.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reinforcement Based Exercise on Fitness and Work Productivity in Adults with Mental Retardation

Abstract: The present study evaluated the effects of a reinforcement based aerobic and resistance exercise program on three obese men with mental retardation and below average fitness levels. A multiple-baseline-across-subjects design was employed to evaluate treatment effectiveness and retention of treatment effects on five dependent measures: body weight, percent body fat (body composition), oxygen consumption (predicted max V̇O2 in ml/kg/min), composite isometric strength (in kg of force), and work productivity (piec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 7 publications
3
24
2
3
Order By: Relevance
“…Rimmer and colleagues [49] found significant improvements in the cardiovascular fitness and muscle strength and endurance of adults with Down syndrome who participated in a cardiovascular and strength exercise training programme. Other studies also showed improvements in muscle strength following training programmes for individuals with Down syndrome [19,20] . Draheim REPORTS bin [50] found reduced risk of hyperinsulinemia and abdominal obesity in adults with mental retardation (with and without Down syndrome) who were moderately to vigorously physically active at least five days per week and consumed lower dietary fat intakes.…”
Section: Benefits From Physical Activity or Exercisementioning
confidence: 98%
“…Rimmer and colleagues [49] found significant improvements in the cardiovascular fitness and muscle strength and endurance of adults with Down syndrome who participated in a cardiovascular and strength exercise training programme. Other studies also showed improvements in muscle strength following training programmes for individuals with Down syndrome [19,20] . Draheim REPORTS bin [50] found reduced risk of hyperinsulinemia and abdominal obesity in adults with mental retardation (with and without Down syndrome) who were moderately to vigorously physically active at least five days per week and consumed lower dietary fat intakes.…”
Section: Benefits From Physical Activity or Exercisementioning
confidence: 98%
“…Not surprisingly, muscle weakness interferes with these individuals' ability to perform tasks of daily living (8,16,39). Reductions in physical function limits opportunities for independent living, vocational opportunity and productivity, and economic self-sufficiency that ultimately lead to assisted living and lower quality of life in this population (17,36,49,51). Furthermore, mobility impairments are predictive of mortality in adults with DS (13).…”
mentioning
confidence: 99%
“…). Second, having greater muscle strength contributes to perform tasks of daily living and/or occupational activities more easily and can even enhance work productivity in individuals with ID (Croce and Horvat ; Seagraves et al . ).…”
Section: Discussionmentioning
confidence: 99%